Consistency of Business Process Models and Object Life Cycles - Ryndina, Ksenia; Küster, Jochen; Gall, Harald (Models in Software Engineering (1st Workshop on Quality in Modeling at MoDELS 2006, Genoa (Italy)))

On the Pitfalls of UML Activity Modeling - Schattkowsky, Tim; Förster, Alexander (Proceedings of the ICSE workshop on Modeling in Software Engineering (MISE 2007), Minneapolis, MN (USA))
With the introduction of new Petri net-like semantics for Activities in UML 2.0, these have become a complete language for modeling behavior. Thus, UML Activities are nowadays investigated for application in many areas from embedded systems to business process modeling. However, some issues have been discovered that currently seem to limit the practical applicability of Activities. In this paper, we present an overview of the identified semantic and syntactic problems, and point at possible solutions and directions for future research.

Strong spin–orbit interactions in carbon doped p-type GaAs heterostructures - Grbić, B.; Leturcq, R.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Aharonov–Bohm oscillations in p-type GaAs quantum rings - Grbić, Boris; Leturcq, Renaud; Ihn, Thomas; Ensslin, Klaus; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

High sensitivity far-infrared detection by resonant inter-Landau-level scattering - Notthoff, C.; Lorke, A.; Reuter, Dirk (Physica E: Low-dimensional Systems and Nanostructures)

Aharonov–Bohm effect of quantum Hall edge channels - Giesbers, A.J.M.; Zeitler, U.; Reuter, Dirk; Wieck, A.D.; Biasiol, G.; Sorba, L.; Maan, J.C. (Physica E: Low-dimensional Systems and Nanostructures)

Magnetic-field-induced modification of the wave-functions in InAs quantum dots - Lei, W.; Wibbelhoff, O.; Notthoff, C.; Marquardt, B.; Reuter, Dirk; Wieck, A.D.; Lorke, A. (Physica E: Low-dimensional Systems and Nanostructures)

Influence of In0.15Ga0.85As capping layers on the electron and hole energy levels of InAs quantum dots - Richter, Mirja; Reuter, Dirk; Duboz, Jean-Yves; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

Capacitance–voltage spectroscopy of post-growth annealed InAs quantum dots - Reuter, Dirk; Roescu, Razvan; Mehta, Minisha; Richter, Mirja; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Site-selective growth of self-assembled InAs quantum dots on focused ion beam patterned GaAs - Mehta, M.; Reuter, Dirk; Melnikov, A.; Wieck, A.D.; Remhof, A. (Physica E: Low-dimensional Systems and Nanostructures)

Quantum dots as tunable scatterers for 2D- and 1D-electron systems - Marquardt, Bastian; Russ, Marco; Lorke, Axel; Meier, Cedrik; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

A comparison: 2D electron- and hole systems in the fractional quantum Hall regime - Hadzibrahimovic, Adriana; Dethlefsen, Annelene F.; Reuter, Dirk; Wieck, Andreas D.; Tranitz, Hans-Peter; Wegscheider, Werner; Haug, Rolf J. (Physica E: Low-dimensional Systems and Nanostructures)

Hot-electron bend resistance in a ballistic GaAs/AlGaAs cross junction - Wiemann, M.; Cetinkaya, A.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Magneto-ballistic effects in non-centrosymmetric GaAs/AlGaAs cross junctions - Wieser, U.; Knop, M.; Kunze, U.; Reuter, Dirk; Wieck, A.D. (Physica E: Low-dimensional Systems and Nanostructures)

Magneto-optical probing of weak disorder in a two-dimensional hole gas - Bryja, Leszek; Wójs, Arkadiusz; Misiewicz, Jan; Potemski, Marek; Reuter, Dirk; Wieck, Andreas (Physical Review B)

Spin-controlled LEDs and VCSELs - Hövel, S.; Gerhardt, N. C.; Brenner, C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W. (physica status solidi (a))

Subsecond Spin Relaxation Times in Quantum Dots at Zero Applied Magnetic Field Due to a Strong Electron-Nuclear Interaction - Oulton, R.; Greilich, A.; Verbin, S. Yu.; Cherbunin, R. V.; Auer, T.; Yakovlev, D. R.; Bayer, M.; Merkulov, I. A.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Sequential and cotunneling behavior in the temperature-dependent thermopower of few-electron quantum dots - Scheibner, R.; Novik, E. G.; Borzenko, T.; König, M.; Reuter, Dirk; Wieck, A. D.; Buhmann, H.; Molenkamp, L. W. (Physical Review B)

Exciton fine structure inInGaAs∕GaAsquantum dots revisited by pump-probe Faraday rotation - Yugova, I. A.; Greilich, A.; Zhukov, E. A.; Yakovlev, D. R.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Robust manipulation of electron spin coherence in an ensemble of singly charged quantum dots - Greilich, A.; Wiemann, M.; Hernandez, F. G. G.; Yakovlev, D. R.; Yugova, I. A.; Bayer, M.; Shabaev, A.; Efros, Al. L.; Reuter, Dirk; Wieck, A. D. (Physical Review B)